Resistance to organizational change: analysis of the process of implementation of the integrated management system in SENAI-BA - Paiva, Danielle Soares; Andrade, José Célio Silveira (Revista de Administração da UFSM, 2013)
More and more, organizations are challenged to anticipate an uncertain future in order to survive in the market, so it is natural that the processes of organizational change part of their routine and it will be perceived resistance from those who takes part the organization. So, this article aims to analyze, though the view internal public, in which perspectives are the main resistances to the organization change in a non-profit organization, upon the implementation of Integrated Management Systems. The present work was realized in Serviço Nacional de Aprendizagem Industrial – Departamento Regional da Bahia (SENAI/BA), over the period of 2006 upon 2009. For this, was realized a bibliography search of organization change and resistance for it. The research was essentially qualitative, with methodologists procedures that had included documentary analysis, the application of the technique of focus groups, interviews and participated observation. From the obtained results, concludes that the main resistance for the organization change, when the implementation of Integrated Management Systems, are concentrated in the politic, human and cultural perspectives.